PENERAPAN METODE INFILTRATION DITCH SEBAGAI USAHA PENURAPAN AIR TANAH UNTUK SUPLAY AIR BERSIH BAGI MASYARAKAT DESA WANGA - Nirmalawati, Nirmalawati (MEKTEK, 2010)
Wanga village, according to geoelectric measurements, has groundwater at depths of > 34 meters such thatit was detected below the surface, and rainfall of 3165 mm/year. This condition makes the groundwaterrecharge area is so big, and will be very potential. But in fact during the dry season, the surface water is notsufficient. The purpose of this research is to assist residents in the village Wanga in providing clean waterusing the application of the method "infiltration ditch". Therefore the lack of clean water can be resolved.The research method used is a research and development where the outcomes are to produce a specificproduct and test the effectiveness of these products. The research shows that the method of infiltration ditchin the provision of clean water in villages Wanga can be applied well in the field according to siteconditions, and will be able to overcome the shortage of clean water. Methods "infiltration ditch" can beapplied in other village locations in the North Lore District area because it has the same ground waterconditions